Belonging in a marginalized neighborhood :|a historical ethnography of Istanbul’s Okmeydanı - Yıldız, Demet. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This thesis studies the contemporary history of Okmeydanı, an urban neighborhood in Istanbul which has a specific place in the history of urbanization in Turkey. Established as a gecekondu settlement during the rural-urban migration period in the late 1950s and 1960s, the neighborhood went through other transformations marked by new waves of migration and the political circumstances surrounding them. Based on the narratives of Okmeydanı’s inhabitants, this study examines the sense of belonging and the sense of community in this place which has been generally approached as one of the marginalized “Alevi-leftist” neighborhoods. To explore how the inhabitants developed an attachment to the neighborhood where they live in, and identify themselves with it, this study focuses on the establishment process of the settlement, and transformations that it went through in the 1990s. Given the diversity of its population and different historical processes, the inhabitants had their own particular experiences of bonding with their new environment after the migration, and thus have different recollections of the past. In addition, by the 2000s, under the impact of globalization, Okmeydanı has become one of the targeted areas for gentrification and urban renewal attempts. This thesis also overviews how the Okmeydanı’s inhabitants defend the identity and texture of their neighborhood against the urban transformation project.
Keywords: Marginality, Social -- Political aspects -- Okmeydanı.; Community development -- İstanbul -- Okmeydanı.